EXPLORING EFL TEACHERS’ UNDERSTANDING AND BELIEFS IN INTERCULTURAL COMMUNICATIVE COMPETENCE IN INDONESIAN CONTEXT - Nisa Hasanah; Wawan Gunawan (University of Kuningan, 2020)
As the result of globalization, the English language teaching goals in many countries have shifted from communicative competence to intercultural communicative competence (ICC). However, among the small number of studies on ICC in Indonesia, most of them focus on ICC in the tertiary level which shows there is a gap of work in the secondary level of education. Thus, this article attempts to seek the truth about senior high school teachers’ understanding and beliefs as well as revealing their attempts in promoting ICC in the classroom. The case study was employed with two novice teachers as participants through interview and document analysis. The finding shows some interesting facts that both teachers viewed concept of ICC similarly as cross-cultural understanding in a way both to overcome misunderstanding and culture shock. Both teachers believed that language is culture bound, yet, only a very small trace of cultural aspects were shown in the documents; and as they viewed culture as dynamic, yet, the content being taught mainly covered static domain of culture. Keywords: Byram’s five savoirs; culture education; intercultural communicative competence.